2003
DOI: 10.1103/physreve.67.061407
|View full text |Cite
|
Sign up to set email alerts
|

Particle aggregation with simultaneous surface growth

Abstract: Particle aggregation with simultaneous surface growth was modeled using a dynamic Monte Carlo method. The Monte Carlo algorithm begins in the particle inception zone and constructs aggregates via ensemble-averaged collisions between spheres and deposition of gaseous species on the sphere surfaces. Simulations were conducted using four scenarios. The first, referred to as scenario 0, is used as a benchmark and simulates aggregation in the absence of surface growth. Scenario 1 forces all balls to grow at a unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 40 publications
5
60
0
Order By: Relevance
“…Recent studies, using numerical simulations of singleparticle trajectories [22,23] and of "lumped" properties with the method of moments [2], suggested a critical importance of interplay among all these individual processes-nucleation, coagulation, and surface growth. Moreover, these results suggested that the transition of spherical, coalescent growth into fractal-like objects is linked directly to the nucleation, as it supplies the abundance of very small primary particles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies, using numerical simulations of singleparticle trajectories [22,23] and of "lumped" properties with the method of moments [2], suggested a critical importance of interplay among all these individual processes-nucleation, coagulation, and surface growth. Moreover, these results suggested that the transition of spherical, coalescent growth into fractal-like objects is linked directly to the nucleation, as it supplies the abundance of very small primary particles.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we combine two techniques, the efficient stochastic particle collision algorithm [3,10] and the sterically-resolved collector-particle simulations [22,23]. In the following, we describe the numerical model, test the accuracy and authenticity of model predictions, and then perform a series of numerical simulations of time evolution of soot particles and their size distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 These models suggest that the synthesis of small carbon-bearing molecules together with their radicals is linked to the formation of PAHs and to the production of soot and possibly fullerenes in hydrocarbon flames. [38][39][40][41][42][43] Various mechanisms have been postulated; those currently in favor are thought to involve a successive buildup of hydrogen-deficient carbon-bearing radicals and molecules via sequential addition steps of small hydrogen-deficient species such as carbon atoms (C), carbon clusters (C 2 , C 3 ), and carbon-bearing doublet radicals including ethynyl (C 2 H), cyano radicals (CN), and phenyl radicals (C 6 H 5 ). [44][45][46][47][48][49][50][51][52][53][54][55][56][57] Upon reaction with closed-shell hydrocarbons and their radicals, these elementary reactions do not only form more complex, closedshell hydrocarbons, but also extremely stable resonantly stabilized free radicals (RSFRs) and aromatic radicals (ARs) [1][2][3][4][5][6][14][15][16][58][59][60][61] In RSFRs, such as in the propargyl radical (C 3 H 3 ), the unpaired electron is delocalized and spread out over two or more sites in the molecule.…”
mentioning
confidence: 99%
“…These high concentrations make them important reactants to be involved in the formation of soot and PAHs. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Here, we review contemporary developments on crossed molecular beam studies that lead to the formation of highly hydrogen-deficient molecules acting as precursors to PAH-like species. In detail, crossed molecular beam reactions of carbon atoms (C), carbon clusters (C 2 , C 3 ), and carbon-bearing doublet radicals including ethynyl (C 2 H), cyano radicals (CN), and phenyl radicals (C 6 H 5 ) will be discussed.…”
mentioning
confidence: 99%